The Influence Of Entrepreneurship Courses On Interest In Entrepreneurship In Students Of The Faculty Of Economics And Business, Bandar Lampung University (Case Study of 2019 Faculty of Economics and Business Students) - Vinsensius Ivan Rianto; Tina Miniawati Barusman (Cita konsultindo, 2024)
The aim of this research is to find out how entrepreneurship courses influence the interest of students at the Faculty of Economics and Business, Bandar Lampung University in this field. The population of 240 students at the Faculty of Economics and Management in 2019 is 175 management students and 65 accounting students. The Accidental Sampling method with the Slovin formula was used to select 71 respondents as research samples. A survey of economics and management faculty students class of 2019 was used as a data source. Primary data collection was carried out by observation, examination of documentation, and questionnaires. The results of this research show that entrepreneurship courses have a positive and significant effect on students' interest in entrepreneurship at the Faculty of Economics and Business, Bandar Lampung University.